A management perspective on the performance of the irrigation subsector - Nijman, C. (International Irrigation Management Institute, 1993)
This study adopts two objectives : !) the identification of generalized directions of management change for performance improvement in the irrigation subsector and 2) the testing of an analytical framework for irrigation management.